2008
DOI: 10.1002/eji.200738099
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of prion and doppel proteins and of their receptors in mouse splenocytes

Abstract: Doppel (Dpl) shares common structural features with the prion protein (PrP) whose pathologic isoform is considered as the causative agent of prion diseases. Although their physiological functions in the immune system remain largely unknown, we demonstrated that substantial amounts of PrP and Dpl are expressed by spleen cells notably B lymphocytes, granulocytes and DC, but not T lymphocytes and NK. To characterize transinteracting partners of PrP and Dpl on mouse splenocytes, fluorescent PrP and Dpl tetramers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Gene expression data reveal that PrP expression is generally down-regulated during granulocyte differentiation [151] though some expression is still detectable [152] (see also Figure 2). Neutrophil functions have been shown to be inhibited by both native and scrapie associated prion protein, resulting in failure of neutrophil aggregation and deficits in superoxide radical and beta-glucuronidase export [153].…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression data reveal that PrP expression is generally down-regulated during granulocyte differentiation [151] though some expression is still detectable [152] (see also Figure 2). Neutrophil functions have been shown to be inhibited by both native and scrapie associated prion protein, resulting in failure of neutrophil aggregation and deficits in superoxide radical and beta-glucuronidase export [153].…”
Section: Resultsmentioning
confidence: 99%
“…Reports linking Doppel protein to the control of Ca 2+ movements in local cell domains, such as the endoplasmic reticulum and the mitochondrial matrix or beneath the plasma membrane, have emerged (Brini et al. 2005; Cordier‐Dirikoc et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, observations in cells and tissues suggest that Doppel may also exist as an intracellular form devoid of the GPI anchor (Peoc’h et al. 2002; Cordier‐Dirikoc et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Doppel is expressed with PrP C in spleen cells, notably B lymphocytes, granulocytes and dendritic cells (Cordier-Dirikoc et al, 2008).…”
Section: Expressionmentioning
confidence: 99%
“…The detection of Prnd mRNA in brain blood vessel endothelial cells might indicate a possible role in the development of brain blood vessels (Li et al, 2000). The observation that Doppel is expressed with PrP C in B lymphocytes, granulocytes and dendritic cells argues for a role in cell-cell interaction in the immunosystem (Cordier-Dirikoc et al, 2008). Several evidence showed that Doppel is able to coordinate in vitro the binding of copper ions with high affinity (Cereghetti et al, 2004;La Mendola et al, 2010;Qin et al, 2003).…”
Section: Functionmentioning
confidence: 99%